Isolation of a Highly Thermostable Bile Salt Hydrolase With Broad Substrate Specificity From Lactobacillus paragasseri - Kusada, Hiroyuki; Arita, Masanori; Tohno, Masanori; Tamaki, Hideyuki (Frontiers in Microbiology, 2022)
Bile salt hydrolase (BSH) enzymes produced by intestinal Lactobacillus species have been recognized as major targets for probiotic studies owing to their weight-loss and cholesterol-lowering effects. In this study, we isolated a highly thermostable BSH with broad substrate specificity, designed as LapBSH (BSH from a probiotic bacterium, Lactobacillus paragasseri JCM 5343T). The recombinant LapBSH protein clearly hydrolyzed 12 different substrates, including primary/secondary, major/minor, and taurine/glycine-conjugated bile salts in mammalian digestive tracts. Intriguingly, LapBSH further displayed a highly thermostable ability among all characterized BSH enzymes. Indeed, this enzyme retained above 80% of its optimum BSH activity even after 6 h of incubation at 50–90°C. LapBSH also exerted a functionally stable activity and maintained above 85% of its original activity after pre-heating at 85°C for 2 h. Therefore, LapBSH is a very unique probiotic enzyme with broad substrate specificity and high thermostability. The strain itself, JCM 5343T, was also found to exhibit high heat-resistance ability and could form colonies even after exposure to 85°C for 2 h. As thermostable enzyme/bacterium offers industrial and biotechnological advantages in terms of its productivity and stability improvements, both thermostable LapBSH and thermotolerant L. paragasseri JCM 5343T could be promising candidates for future probiotic research.